The Relationship Between Loneliness and Psychological Adjustment: Validation of the Italian Version of the Interpersonal Acceptance–Rejection Loneliness Scale - Senese, Vincenzo Paolo; Nasti, Carla; Mottola, Francesca; Sergi, Ida; Massaro, Rita; Gnisci, Augusto (Frontiers in Psychology, 2021)
In the recent literature, many researchers have highlighted that the feeling of loneliness can be considered a relevant psychological distress with short- and long-term consequences on people's health, that needs to be appropriately monitored and treated. In this view, the Interpersonal Acceptance-Rejection Loneliness Scale (IPARLS) has been developed to evaluate the subjective feelings about the psychological distress associated with interpersonal loneliness and to overcome the limits of the previous scales; however, its psychometric characteristics have not yet been fully investigated. Starting from these considerations, two studies have been conducted. A first study, involving 688 adults (19-69 years; 51% females), to assess dimensionality, reliability, validity, and test the measurement invariance of the Italian version of the IPARLS. A second study, involving 205 adults (20-69 years; 51% females), to investigate the relationship between loneliness and psychological adjustment. Results confirmed the unidimensionality of the scale and showed that it is reliable, valid and fully invariant as a function of age and gender. Moreover, data showed a strong association between perceived loneliness and psychological adjustment. The IPARLS scale is confirmed to be a valid tool to investigate loneliness in the life cycle both from a clinical and a research point of view.